"Shared sense of purposefulness": a new concept to understand the practice of coordinating design in construction. Issue 1 (2nd January 2020) - Çıdık, Mustafa Selçuk; Boyd, David
Abstract: Construction management literature sees the collective task of coordinating design as being about the "'integration'" of "fragmented" discipline-specific design tasks/outputs, thus overlooking the important role of social interactions. This is not only conceptually problematic but also presents a practical management problem. As a response, a practice-based approach, which relies on a "becoming" ontology, is adopted for a practical explanation of design coordination for more effective design management. The adopted methodology suggests that design develops as a result of unfolding (path-dependent) individual actions and interdisciplinary interactions. Based on this, the concept of a "shared sense of purposefulness" is proposed to refer to the temporary and precarious organizational state of a design team in which each of the interacting team members has achieved a state of purposefulness to resume individual action. Hence, design coordination in construction is redefined as continuously re-establishing and maintaining "a shared sense of purposefulness". The concept's usefulness for understanding the practice of design coordination is demonstrated using data collected from a project in the UK. The discussion enables fresh insights into the everyday operation of design coordination. It is concluded that the proposed conception paves a way forward both for the research and practice in construction design management.